THE DESIGN OF PULPER MACHINE TO INCREASE COFFEE PRODUCTION CAPACITY IN REALIZING PEOPLE'S ECONOMY - Kiromim Baroroh; Sutopo Sutopo; Aprilia Tina Lidyasari; Eva Imania Eliasa; Khairul Irsad; Nugroho Suryo Pambudi; Devi Kusumawati; Richa Lailil Ulya (Jurnal Dinamika Vokasional Teknik Mesin, 2023)
The planning and making of the peeler machine for coffee skin are aimed at completing the needs of SMEs at Pagerharjo, Samigaluh, Kulonprogo. The manual process is the main obstacle in peeling coffee sheets in SMEs. The main objective of creating technological innovation is to assist workers in the production process using appropriate technology to make their work more qualified, effective, and efficient. In planning and making coffee pulper, we must study some literature, make plans, calculate the process of creating tools, and evaluate the tools' trial and error. The picture design use application, namely Autodesk Inventor. The size of the machine is 110 cm x 127 cm x 130 cm; using a motor with gas oil, and the first circle is 3600 rpm, used to pull components with the ratio 1:6, v-belt the type A 75, one solid ship with the diameter of 20 mm. the final result is that the capacity of the pulper machine for coffee is 610 kg/hour.